Patients' Perspectives on the Usability of a Blended Approach to an Integrated Intervention for Patients With Medically Unexplained Physical Symptoms: Mixed Methods Study - Suze Adriana Johanna Toonders; Paula Elisabeth van Westrienen; Sophie Konings; Marianne E Nieboer; Cindy Veenhof; Martijn F Pisters (JMIR Publications, 2021)
BackgroundMedically unexplained physical symptoms are physical symptoms, such as pain, fatigue, and dizziness, that persist for more than a few weeks and cannot be explained after adequate medical examination. Treatment for preventing the chronicity of symptoms is recommended. A promising approach is identifying patients who are at risk and subsequently offering a blended care intervention that focuses on promoting self-management while using eHealth as a supportive tool. When these interventions match with a patient's expectations, their effectiveness grows. ObjectiveThis study aimed to obtain more insights into usability from the patient perspective to improve future interventions. MethodsA mixed methods design (ie, the use of qualitative and quantitative data) was used. Through semistructured interviews, in-depth insights were gained into patients' perspectives on usability. The analysis process was continuous and iterative. Data were synthesized and categorized into different themes. The System Usability Scale, which measures the usability of a system, was used to compare participants that found usability to be low, medium, or high. This study was approved by the Medical Ethical Committee Utrecht (approval number: 17-391/C). ResultsSaturation was reached after interviewing 13 participants. The following four themes emerged from the interviews: motivations and expectations prior to participating in the program, the applicability of e-coaching, the role of health care professionals, and the integrated design of the blended approach. ConclusionsThe successful implementation of integrated blended care interventions based on patients' perspectives requires matching treatments to patients' individual situations and motivations. Furthermore, personalizing the relative frequency of face-to-face appointments and e-coaching can improve usability.